INSULIN RESISTANCE AND ELECTROCARDIOGRAPHIC ALTERATIONS IN NON-OBESE INDIAN PATIENTS WITH HYPERTENSION - Rajeev Kumar (Student's Journal of Health Research, 2023)
Background:  Heart disease risk has been associated with cardiac steatosis. The relationships between cardiac steatosis, aberrant electrocardiograms (ECG), and specific metabolic syndrome symptoms (MetS) were studied. Method:  This prospective study was conducted from July 2021 to August 2022 at Patna Medical College & Hospital, Patna, and laboratory data and a 10-lead ECG were compared between 35 men without the MetS and 30 men with the MetS. Using 1.0 T magnetic resonance (MR) spectroscopy, the myocardial triglyceride (MTG) content was determined, and epicardial and pericardial fat was imaged using MR. SPSS 22.0 for Windows was used to conduct all statistical analyses. The Kolmogorove-Smirnov test was used to determine whether continuous variables were normal. Results:  Compared to participants without the MetS, men with the condition exhibited higher levels of MTG in their epicardial and pericardial fat depots (p <0.002). Patients with MetS had greater heart rates (p <0.002), longer PR intervals (p <0.043), a shift of the frontal plane QRS axis to the left (p <0.002), and lower QRS voltage (p <0.002). There was an inverse relationship between the frontal plane QRS axis and the QRS voltage and MTG content, waist circumference (WC), body mass index (BMI), TGs, and fasting blood glucose. Measures of insulin resistance were associated adversely with the QRS voltage, but high-density lipoprotein cholesterol correlated positively. The frontal plane QRS was determined by the MTG content and hypertriglyceridemia, while the QRS voltage was predicted by the WC and hyperglycemia. Conclusion:  Several alterations on the 10-lead ECG appear to be related to both the MetS and cardiac steatosis. In people with MetS, the frontal plane QRS axis is displaced to the left and the QRS voltage is reduced. In obese people with cardiometabolic risk factors, the presence of left ventricular hypertrophy may be understated by standard ECG criteria.